2009
DOI: 10.1111/j.1442-2042.2008.02244.x
|View full text |Cite
|
Sign up to set email alerts
|

Urates in uric acid renal calculi

Abstract: Objectives:To investigate the presence of calcium urate, sodium, potassium and calcium in 'pure' uric acid calculi. Methods: Ten spontaneously passed uric acid urinary calculi have been examined by stereoscopic microscopy, infrared spectroscopy, scanning electron microscopy and energy dispersive X-Ray analysis. Results: The analysis of selected uric acid calculi revealed the presence of a near-pure calcium urate in two cases and of calcium enriched urate zones in all of the samples. Furthermore, in some cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…We acknowledge that not all of the crystals we have found may be MSU monohydrate. Urates aside from MSU, including calcium urate, potassium urate and magnesium urate, are known to form within the urinary tract leading to renal calculi47 48 and could be contributing to this other type of crystal seen in renal tophi and other tissues as well. Additionally, urate is a well-known chelator of metal ions such as zinc, copper and iron, and may form salts of metallourate complexes 49 50.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that not all of the crystals we have found may be MSU monohydrate. Urates aside from MSU, including calcium urate, potassium urate and magnesium urate, are known to form within the urinary tract leading to renal calculi47 48 and could be contributing to this other type of crystal seen in renal tophi and other tissues as well. Additionally, urate is a well-known chelator of metal ions such as zinc, copper and iron, and may form salts of metallourate complexes 49 50.…”
Section: Discussionmentioning
confidence: 99%
“…6 Most urinary uric acid calculi are not pure in composition and complex urates, sodium, potassium, and calcium have been found together in various proportions. 7 An analysis of stones in gout patients in Japan showed that the incidence of common calcium salt stones was over 60%, while that of uric acid stones was only 30%. 8 This implies that the disruption of uric acid metabolism promotes not only uric acid stones, but also calcium salt stones.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years more publications concerning the composition of kidney stones have been published. These publications address the causes of kidney stone disease and its relationship with metabolic syndrome [1,[7][8][9][10][11][12]. Nevertheless, the data concerning the relationship of metabolic syndrome and type of kidney stone remain contradictory.…”
Section: Introductionmentioning
confidence: 99%